2019
DOI: 10.1007/s00382-019-05086-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate shift of the South China Sea summer monsoon onset in 1993/1994 and its physical causes

Abstract: The characteristics of anomalous circulations during spring associated with the climate shift of the South China Sea summer monsoon (SCSSM) onset in 1993/1994 and its physical causes are investigated. It is found that the interdecadal shift of SCSSM onset happened in 1993/1994 is related closely to the 850 hPa zonal wind anomalies over the area around Kalimantan Island. Easterly (westerly) anomalies over Kalimantan Island enhance (weaken) subtropical high over the western North Pacific, leading to the late (ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The averaged onset dates are 26 May and 13 May during the two epochs, respectively. The interdecadal shift of SCSSM onset date around 1993/1994 is statistically significant at 95% confidence level according to the Student's t test, and this result is consistent with other studies (Kajikawa and Wang, 2012;Yuan and Chen, 2013;Lin and Zhang, 2020).…”
Section: Scssm Onset-related Interdecadal Change Of Mid-upper Tropospsupporting
confidence: 91%
See 1 more Smart Citation
“…The averaged onset dates are 26 May and 13 May during the two epochs, respectively. The interdecadal shift of SCSSM onset date around 1993/1994 is statistically significant at 95% confidence level according to the Student's t test, and this result is consistent with other studies (Kajikawa and Wang, 2012;Yuan and Chen, 2013;Lin and Zhang, 2020).…”
Section: Scssm Onset-related Interdecadal Change Of Mid-upper Tropospsupporting
confidence: 91%
“…Yuan and Chen (2013) further explained that the interdecadal warming of the tropical western Pacific leads to active convection over there and early eastward retreat of the western Pacific subtropical high, which favors the early onset of the SCSSM. Lin and Zhang (2020) suggested that the interdecadal warming over the western equatorial Pacific modulates the low-level zonal winds around the Kalimantan Island, which affects the subtropical high and the interdecadal advanced SCSSM onset. Xiang and Wang (2013) found more specific results that the early onset of the summer monsoon in the Arabian Sea and the Bay of Bengal is mainly regulated by the zonal sea surface temperature (SST) gradient in the equatorial Pacific, while the early onset of the SCSSM is mainly attributed to the positive SST anomaly near the Philippine Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have discussed the role of the meridional gradient of zonal winds in the interdecadal variability of SCSSM. Lin and Zhang found that SST anomalies in the key region (140°–150°E, 5°S–2.5°N) have a significant correlation with the meridional gradient of zonal wind in the SCS, resulting in an obvious shift of SCSSM onset (Lin & Zhang, 2020). Generally, vorticity comprises two terms: the meridional gradient of zonal winds (u/y) and the zonal gradient of meridional winds (v/x).…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Previous studies have revealed that the extreme events in China are associated with the East Asia summer monsoon (EASM) (Wang [32] ; Yin et al [33] ), the South China Sea summer monsoon (SCSSM) (Chen et al [34] ; Lin and Zhang [35] ), the Southwest Australian monsoon circulation (SWAC) (Feng et al [36] ), the western north Pacific subtropical high (WNPSH) (Choi and Kim [37] ), and the sea surface temperature (SST) anomaly of the tropical Indian Ocean (TIO). Specifically, the stronger EASM pushes the rainfall front to the northwest, pushing a large amount of water vapor over East Asia (Lau and Li [38] ).…”
Section: Introductionmentioning
confidence: 99%